W-band high output power Schottky diode doublers with quartz substrate - 姚常飞 周明 罗运生 李姣 许从海 (Journal of semiconductors, 2013)
W-band quartz based high output power fix-tuned doublers are analyzed and designed with planar Schot- tky diodes. Full-wave analysis is carried out to find diode embedding impedances with a lumped port to model the nonlinear junction. Passive networks of the circuit, such as the low pass filter, the E-plane waveguide to strip transitions, input and output matching networks, and passive diode parts are analyzed by using electromagnetic simulators, and the different parts are then combined and optimized together. The exported S-parameters of the doubler circuit are used for multiply efficiency analysis. The highest measured output power is 29.5 mW at 80 GHz and higher than 15 mW in 76-94 GHz. The highest measured efficiency is 11.5% at 92.5 GHz, and the typical value is 6.0% in 70-100 GHz.